2019
DOI: 10.1111/1460-6984.12486
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in aphasia outcomes: evidence from the AphasiaBank

Abstract: Background: Stroke is one of the leading causes of death in the United States. Aphasia is a language impairment which results as a consequence of stroke. Gender differences are reported in underlying mechanisms of stroke, however, gender differences in aphasia type and severity remain unclear. Aims: To examine gender differences in aphasia impairment based on data from AphasiaBank, a research repository of data obtained from studies of aphasia. Methods & Procedures:The data were collected from AphasiaBank for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The most classic type of nonfluent aphasia is broca aphasia, which is characterized by poor oral fluency and retelling ability and relatively good listening and understanding ability, which damages broca's brain area and affects the continuity of language [ 62 , 63 ]. After analysis by Sharma et al[ 10 ], it was found that the incidence of broca aphasia in men (27.4%) was significantly higher than that in women (19.2%), with an average age of 61.9 years. At present, the mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most classic type of nonfluent aphasia is broca aphasia, which is characterized by poor oral fluency and retelling ability and relatively good listening and understanding ability, which damages broca's brain area and affects the continuity of language [ 62 , 63 ]. After analysis by Sharma et al[ 10 ], it was found that the incidence of broca aphasia in men (27.4%) was significantly higher than that in women (19.2%), with an average age of 61.9 years. At present, the mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The severity and age of stroke can predict the risk of PSA [ 7 , 8 ], and the location and size of stroke have an important reference role in predicting PSA types [ 9 ]. But whether gender plays a predictive role in the incidence of PSA and its types is still controversial [ 10 , 11 ]. The lateralization of cerebral hemisphere use and the onset age of stroke affect the incidence of PSA in different sexes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data for this study were drawn from the Mandarin protocol of the AphasiaBank database located in the TalkBank System (Chen et al., 2018; Deng et al., 2021). AphasiaBank is a shared database that offers researchers a large corpus with a definitive goal to improve the treatment of aphasia by comparing discourse natures from patients with aphasia and individuals without aphasia (Fromm et al., 2020; MacWhinney & Fromm, 2016; MacWhinney et al., 2011; Sharma et al., 2019). The database emphasizes the collection of data based on a specified elicitation protocol that requires the investigator to follow a script for asking questions and eliciting narratives, which offers multimedia information including transcripts of discourse by specific tasks (Fromm et al., 2020; MacWhinney, 2019; MacWhinney & Fromm, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sex/gender differences have also been reported among individuals with aphasia, although the evidence has been mixed. Sharma et al (2019) found greater impairment among men when compared to women in a study of 294 individuals with aphasia using data from the AphasiaBank (Sharma et al, 2019). However, other studies have generally reported no differences in the aphasia outcomes between men and women (Schehter et al, 1985;Sundet, 1988).…”
Section: Social Determinants Of Health and Aphasia Outcomesmentioning
confidence: 95%